2015
DOI: 10.1245/s10434-015-4818-3
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Significance of Sarcomatous Change in Patients with Hepatocellular Carcinoma After Surgical Resection

Abstract: The presence of SC in HCC was uncommon, and was associated with much poorer prognosis than ordinary HCC. Radical resection with negative margin is essential for improving the prognosis. Future prospective studies are warranted to determine if recurrent patients can benefit from postoperative adjuvant therapies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
29
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(32 citation statements)
references
References 25 publications
3
29
0
Order By: Relevance
“…The incidence of sarcomatoid hepatocellular carcinoma (SHC) is quite low with ~2% in surgically resected cases and ~10% in autopsied cases 5, 6 . Although SHC is a very rare histologic variant of hepatocellular carcinoma (HCC), the prognosis of patients with the SHC was significantly worse than ordinary HCC cases 5, 7 . The poor prognosis has been attributed to the highly metastatic property of sarcomatous cells 8, 9 .…”
Section: Introductionmentioning
confidence: 99%
“…The incidence of sarcomatoid hepatocellular carcinoma (SHC) is quite low with ~2% in surgically resected cases and ~10% in autopsied cases 5, 6 . Although SHC is a very rare histologic variant of hepatocellular carcinoma (HCC), the prognosis of patients with the SHC was significantly worse than ordinary HCC cases 5, 7 . The poor prognosis has been attributed to the highly metastatic property of sarcomatous cells 8, 9 .…”
Section: Introductionmentioning
confidence: 99%
“…Previous investigators compared OS between patients with HCC with SC and ordinary HCC, whereas others analyzed the differences between ICC with SC and ordinary ICC. [8][9][10] In those studies, OS of patients with PLC-SC was significantly poorer than that of patients with ordinary HCC and ICC. [8][9][10] In our study, PLC-SC that included a large area of SC and large tumor size showed poorer prognosis than other PLC-SC.…”
Section: Discussionmentioning
confidence: 90%
“…[8][9][10] In those studies, OS of patients with PLC-SC was significantly poorer than that of patients with ordinary HCC and ICC. [8][9][10] In our study, PLC-SC that included a large area of SC and large tumor size showed poorer prognosis than other PLC-SC. Several previous studies suggested that the only way of improving prognosis in PLC-SC is early detection and complete resection of the tumor.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…In the group of PHSs, recent studies have suggested that a combination of surgery and pre-or post-surgical chemotherapy can substantially improve clinical outcomes of the UES. For unresectable tumors, systemic chemotherapy and local radiotherapy can be options [7]. In the case of PHSCs, surgery would be justi ed as the primary treatment.…”
Section: Introductionmentioning
confidence: 99%